The synthesis of chromophore ended glycoles, part IV.: Bis-coumarin derivatives ended polyglycols - Tuncer, Huelya; Erk, Cakil (Wiley, 2006)
The coumarin derivatives of bis-resorcin ended polyglycols were prepared in two ways: Bis-4-alkyl-7-oxycoumarin ended mono and diethyleneglycols were prepared starting from bis(3-hydroxyphenyl)glycols by coumarin condensation using relevant beta-ketoesters. Accordingly, 4-methyl, 4-trifluoromethyl, 4-n-propyl and 4-phenyl derivatives of 7-hydroxycoumarins were prepared in good yields. They were then converted to bis-coumarin ended three and tetraethylenglycol derivatives by reacting with three and tetraethyleneglycols dichlorides in Na2CO3/DMF, respectively. The products were identified using IR, H-1 nmr and low resolution mass spectrometry. The Li+, Na+ and Rb+ metal/Ligand selectivities of cation binding behaviour of products in acetonitrile were studied with steady state fluorescence spectroscopy.
Keywords: Crown-Ethers; Cation-Binding; Recognition